ปัจจัยที่มีผลต่อโครงสร้างเงินทุนของบริษัทจดทะเบียน ในตลาดหลักทรัพย์แห่งประเทศไทย กลุ่มดัชนี SET CLMV - กรรณิกา, วิชุดา; บานชื่นวิจิตร, วรรณรพี (วารสารสหวิทยาการสังคมศาสตร์และการสื่อสาร, 2019)
The objective of this research was to study factors affecting capital structure of listed companies in SET CLMV in the Stock Exchange of Thailand. This research quarterly collected secondary data of financial statements from 24 companies during 2013 to 2017. Descriptive statistics and multiple regressions with pooled OLS, random-effects and fixed-effects tests were used to analyze the data. The results show that firm size, current ratio and times interest earned statistically and significantly affected capital structure. In addition, firm size negatively affected short-term debt to total asset ratio, but positively affected long-term debt to total asset ratio. Current ratio negatively affected short-term debt to total asset ratio and total debt to total asset ratio, but positively affected long-term debt to total asset ratio. Times interest earned negatively affected short-term debt to total asset ratio, long-term debt to total asset ratio and total debt to total asset ratio.